Barriers to healthcare and health seeking behaviors among elderly people living in rural regions of India: a study based on 9 villages in Eastern Uttar Pradesh - Zaidi, Ilham; Chaudhary, Shikhar; Sharma, Twinkle; Vardha, Jagadeswari; Khayum, Abdul; Anjum, Sahifa; Bakshi, Aditi; Nuguru, Gayathree (International Journal Of Community Medicine And Public Health, 2024)
Background: The elderly population in India is experiencing exponential growth and facing various health and well-being challenges. This demographic shift is especially pronounced in rural areas, affecting social, financial, family, and transportation aspects, subsequently impacting health and well-being. This study aims to comprehensively understand these needs and priorities by exploring the multifaceted challenges faced by the elderly in India. Methods: An exploratory qualitative research study with a quantitative component was conducted in 9 villages in Uttar Pradesh’s Siddhartha Nagar District. Participants included individuals aged 60 years and above (n=29, M:F ratio of 13:16). Data were collected using Focus Group Discussions and Personal Interviews to assess the challenges faced by the geriatric population. The methodology involved multi-directional interactive sessions focusing on health, illness, and coping. Results: Participants averaged over 5.8 medical conditions. Those with better Socio-Economic Status (SES) reported multiple conditions but fewer troubles, while the majority, being very poor, did not consider health a primary concern. There were no complaints about the lack of public health facilities or transportation. The study highlights the complex interactions between healthcare, family, and financial difficulties that older people in rural India experience, underscoring the need for specialised treatments. The low level of knowledge about government programmes emphasises the need for improved outreach techniques to close existing accessibility gaps. Conclusions: The study recommends focused interventions and improved policies to meet the unique needs of India's rural elderly population. Policymakers and healthcare providers can enhance the well-being of this vulnerable demographic by understanding the complex nature of their issues.